The Effect Of The Barman Model On The Acquisition Of Concepts And Attitudes Towards The Subject Of Aesthetics Among Students Of The Department Of Art Education (Journal of the College of Basic Education, 2024)
The current research seeks to identify the effect of the Barman model on the acquisition of concepts and attitudes toward the subject of aesthetics among students of the Department of Art Education. In order to achieve the objectives of the current research, the researcher followed the steps of the semi-experimental approach through two experimental and control groups amounting to (86) divided equally into both groups. The third grade in the Art Education Department and sections (A) and (B) were chosen to be the research sample. The researcher built a test to measure concepts in the subject of aesthetics, as well as a measure of attitude towards the subject, and verified the psychometric properties. After applying the experiment, the study reached the following results:The Barman model has an impact on the experimental group students’ acquisition of concepts in the subject of aestheticsThe Barman model achieves positive attitudes towards the subject of aesthetics for students in the experimental group compared to the control group.